Understanding community pharmacists’ intentions to report adverse drug reactions in Saudi Arabia: a theory of planned behavior analysis - Alsulami, Fahad T.; Alqarni, Yousef Saeed; Alruqayb, Wadia Saad; Alharthi, Mohammed S.; Alzahrani, Mohammad S.; Algarni, Majed A.; Althobaiti, Musaad M.; Almalki, Saad Mohammed; Altowarqi, Nawaf Abid; Mathkur, Hussain Ali; Althumali, Anas Muslih; Alharthi, Ayman Mohammed; et al. (Frontiers in Pharmacology, 2025)
IntroductionAdverse drug reaction (ADR) reporting is critical for ensuring medication safety. However, underreporting remains a global concern, particularly in community pharmacy settings. This study explores the behavioral factors influencing community pharmacists’ intention to report ADRs in Saudi Arabia, using the Theory of Planned Behavior (TPB) as a guiding framework.Aims and ObjectivesThis study aimed to estimate factors affecting community pharmacists’ intention to report ADRs to the Saudi National Pharmacovigilance Center (NPC) through a TPB-based analysis.MethodsA cross-sectional survey was conducted to collect data on pharmacists’ intentions, attitudes, subjective norms, perceived behavioral control, and moral obligation regarding ADR reporting. Descriptive statistics summarized the sample characteristics. Binary logistic regression was used to evaluate the influence of TPB constructs on reporting intentions.ResultsAmong 452 participating community pharmacists, 88% were aware of the NPC, but only 27.4% had reported ADRs in the past year. Pharmacists who were non-Saudi, aware of the NPC and its procedures, and trained in ADR reporting demonstrated significantly higher intentions to report (p < 0.05). Attitudes (OR = 1.141, 95% CI: 1.09–1.18, p < 0.001), subjective norms (OR = 1.280, 95% CI: 1.16–1.40, p < 0.001), perceived behavioral control (OR = 1.168, 95% CI: 1.03–1.31, p = 0.010), and moral obligation (OR = 1.417, 95% CI: 1.05–1.89, p = 0.019) were all significantly associated with reporting intention.ConclusionFindings reinforce the importance of targeting TPB constructs (particularly attitudes, social norms, and perceived control) and perceived moral obligation in designing interventions to improve ADR reporting. Strategies such as structured training, institutional support, and promoting moral responsibility may bridge the gap between awareness and actual reporting practices among community pharmacists in Saudi Arabia.